Training peer educators to promote self-management skills in people with serious mental illness (SMI) and diabetes (DM) in a primary health care setting. Issue 2 (7th April 2014) - Blixen, Carol; Perzynski, Adam; Kanuch, Stephanie; Dawson, Neal; Kaiser, Denise; Lawless, Mary E.; Seeholzer, Eileen; Sajatovic, Martha
<x content-type="archive" xml:space="preserve">Abstract</x> Aim To describe the training and participant experience of patients with both severe mental illness (SMI) and diabetes (DM) who were enrolled in a Peer Educator Training Program adapted to a primary health care setting. Background The mortality of patients with both SMI and DM is high. Illness self-management includes medications, psychosocial treatments, and healthy behaviors, yet treatment engagement is often sub-optimal with adherence rates of 52% for diabetic medications and 62% for antipsychotic medications among the SMI. To address this problem, a new behavioral intervention study targeting SMI and DM self-management used trained peer educators (PEs) with the same chronic conditions to enhance program effectiveness. A manual facilitated training on intervention topics such as SMI and DM therapies, stress management, and stigma reduction as well as training in group intervention techniques, telephone skills, and crisis management. Methods We assessed PE attitudes and input using in-depth face-to-face interviews. Interviews were audio-taped, transcribed, coded, and analyzed using the classic method of content analysis emphasizing dominant themes. A member check-in was conducted where participants commented on analysis results. Findings Six relevant descriptive themes emerged: (1) positive group experience; (2) success with learning manual content; (3) increased knowledge about SMI and DM; (4) improved self-management skills; (5) increased self-confidence and self-efficacy in becoming a PE; and being (6) united in purpose to help others self-manage their SMI and DM. Qualitative evidence supports structured training for SMI-DM PEs. Key components include written educational materials and the power of the group process to increase knowledge, self-management skills, confidence, and self-efficacy. Recommendations are offered to support further endeavors to mobilize peers with SMI to help other patients with complex comorbidities better manage their own health.